1995
DOI: 10.1002/jmv.1890450104
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic mumps virus reinfections

Abstract: Although natural mumps virus infection is believed to induce lifelong immunity, our laboratory was confronted with 82 patients who developed mumps-evoking lesions but exhibited serological evidence of a booster immune response, namely a rise or a high titer of virus-specific IgG, without IgM. In order to provide arguments favoring the existence of recurrent mumps attacks, the age, symptomatology, and humoral response of these patients (group 1) were compared to that of 82 randomly selected true primary infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…It is striking that 4 out of the 7 unvaccinated mumps cases were aged 40 years, and it is likely, although not certain, that these persons had encountered wild-type mumps virus earlier in life. However, although natural infection with mumps is thought to confer lifelong protection, incidentally cases of reinfections have been described, [26][27][28] and with the absence of circulating wild-type mumps virus also naturally-acquired immunity against mumps may diminish. In addition, it must be kept in mind that in our assays antibodies were measured against the mumps vaccine strain, which may result in a relatively lower response in persons with naturally-acquired immunity induced by other mumps virus strain(s).…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that 4 out of the 7 unvaccinated mumps cases were aged 40 years, and it is likely, although not certain, that these persons had encountered wild-type mumps virus earlier in life. However, although natural infection with mumps is thought to confer lifelong protection, incidentally cases of reinfections have been described, [26][27][28] and with the absence of circulating wild-type mumps virus also naturally-acquired immunity against mumps may diminish. In addition, it must be kept in mind that in our assays antibodies were measured against the mumps vaccine strain, which may result in a relatively lower response in persons with naturally-acquired immunity induced by other mumps virus strain(s).…”
Section: Discussionmentioning
confidence: 99%
“…Although antigen drift has been hypothesized as a logical culprit, it has been repeatedly shown that the most divergent strains can be neutralized in vitro with only slight variations in serum titers (typically 2-to 8-fold) (13)(14)(15). The observation that naturally acquired wild-type mumps infection does not necessarily confer life-long protection (16,17) suggests that the immune memory to mumps may be inherently unreliable and that breakthrough infection among certain vaccinated individuals could arguably be expected. Furthermore, estimates of mumps vaccine efficacy among two-dose recipients vary, but most are approximately 90% (10,18).…”
mentioning
confidence: 99%
“…Hersh et al initially investigated a large mumps outbreak (n ϭ 269) in Kansas and attributed the resurgence of mumps to primary vaccine failure or failure to vaccinate but did not rule out the possibility that secondary vaccine failure could have played a part in the outbreak (15). Mumps reinfection was also discussed by Gut et al who reported 82 mumps patients with evidence of a booster immune response similar to that in the outbreak described in this paper (13). Our data suggest that waning immunity (secondary vaccine failure) was the main cause of the outbreak in the West Bank refugee camps and they underscore the need for a second vaccine dose as part of the standard immunization program.…”
Section: Discussionmentioning
confidence: 84%
“…Whether mumps secondary vaccine failure (reinfection) occurs is controversial (13,15,26). Hersh et al initially investigated a large mumps outbreak (n ϭ 269) in Kansas and attributed the resurgence of mumps to primary vaccine failure or failure to vaccinate but did not rule out the possibility that secondary vaccine failure could have played a part in the outbreak (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation